Advancements in TDP-43 research: Towards biomarkers and therapeutic targets for amyotrophic lateral sclerosis - Yuhan Wu; Jie Wang; Qianhua Zhao (Aging and Health Research)
Amyotrophic lateral sclerosis (ALS) remains a devastating neurodegenerative disease characterized by progressive motor neuron degeneration, leading to paralysis and premature death. Despite advances in understanding its pathology, ALS diagnosis and treatment remain primarily symptomatic, lacking disease-specific biomarkers. TAR DNA-binding protein 43 (TDP-43) has emerged as a central player in ALS pathogenesis, undergoing pathological alterations including hyperphosphorylation, truncation, and cytoplasmic aggregation. This article reviews the physiological and pathological roles of TDP-43, its potential as a biomarker, and its candidacy as a therapeutic target. Challenges in detecting pathological forms of TDP-43 in biofluids hinder diagnostic advancements, yet recent research provides insights into its potential diagnostic and prognostic value. Moreover, ongoing efforts aim to develop targeted therapies, including genetic and proteostasis-based approaches, to mitigate TDP-43 pathology and its downstream effects. The article also discusses the need for novel animal models and antibodies to distinguish between pathological and physiological forms of TDP-43 for reliable biomarker development. Looking ahead, the article advocates for both linear and horizontal developments in TDP-43 research to advance ALS diagnosis, prognosis, and treatment paradigms.